Business systems for microcomputers : concept, design, and implementation - Haueisen, William D. 4 0 16; Camp, James L.; 5 (Englewood Cliffs, New Jersey : Prentice-Hall, Inc., 1982)
Presents a Management Information System with 11 subsystems for use in managing a business.
Includes index.
Young Adult.
Keywords: 2 -- 0; 6; Data processing.;Data processing. -- Business;Microcomputers.;Business;Personal computers; 20; 2